2021
DOI: 10.1177/19714009211041520
|View full text |Cite
|
Sign up to set email alerts
|

Early institutional experience using the TracStar Large Distal Platform in endovascular flow diversion

Abstract: Introduction The delivery of flow-diverting stents (FDS) necessitates a degree of catheter support beyond that required for endovascular coiling. The TracStar Large Distal Platform (LDP) is a novel 0.088″ platform intended for navigation into the intracranial internal carotid artery (ICA). We present an early institutional experience using the TracStar LDP in 44 cases of endovascular aneurysm embolization using FDS. Methods Inclusion criteria for this single-center retrospective review encompassed all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…9 Likewise, Bageac et al reported their experience in 42 patients with using a new 0.088 ′′ ID AC, via a femoral approach, for flow diversion; they reported a dissection rate of 2.3% (1/44 interventions). 11 Thus, the BMX96 has a complication rate that is similar to those reported for other neurointerventional ACs with a similar but smaller ID. Although some other larger ACs (i.e.…”
Section: Advantages Of the Bmx96supporting
confidence: 68%
See 1 more Smart Citation
“…9 Likewise, Bageac et al reported their experience in 42 patients with using a new 0.088 ′′ ID AC, via a femoral approach, for flow diversion; they reported a dissection rate of 2.3% (1/44 interventions). 11 Thus, the BMX96 has a complication rate that is similar to those reported for other neurointerventional ACs with a similar but smaller ID. Although some other larger ACs (i.e.…”
Section: Advantages Of the Bmx96supporting
confidence: 68%
“…10 Bageac et al reported use of another 0.088 ′′ ID AC, via a femoral approach, in 44 flow diversion cases; the success rate was 97.7% and the combined rate of type II or III aortic arch was 54%. 11 Thus, technical success rates may be a function of both underlying tortuosity and approach. Two successful conversions in our series were initially attempted radially with the LB-AC without success, but then the target vessel was achieved via a femoral approach, suggesting that the combination of vessel tortuosity (subclavian kink plus type II aortic arch, or type III aortic arch) and radial access was not ideal for those cases.…”
Section: Technical Success and Tortuositymentioning
confidence: 99%
“…These results suggest the TracStar LDP may provide additional benefits in other neurointerventional procedures such as aneurysm embolization, where superior distal access and proximal support is also desired – as demonstrated by Bageac et al in the use of the Tracstar LDP for endovascular placement of flow diverting stents. 11…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of neuroendovascular devices requires a catheter access platform which features robust proximal and distal support, and trackability through tortuous vasculature. [1][2][3][4] These requirements have been commonly met by the use of a triaxial system consisting of a guide catheter, intermediate catheter, and a microcatheter system. 5 6 An 0.088 inch (8Fr) guide catheter is often used in these set-ups to provide proximal support while traversing the aortic arch and large proximal vessels, with smaller diameter intermediate catheters used to provide distal support closer to the site of intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The TracStar Large Distal Platform (LDP) (Imperative Care, Campbell, California, USA) is the first ever supportive 0.088 inch guide catheter with a hyperflexible tip designed to track to the intracranial vasculature. 3 This catheter is 105 cm in length and has a unique angled tip, and proprietary durometer transitions facilitate navigation into the cavernous internal carotid artery (ICA) which offer improved stability across major vessels and may provide improved stability for the delivery of large diameter neurointerventional devices. Furthermore, intracranial positioning of an 0.088 inch guide may provide a similar level of distal support to triaxial systems and enable a simplified biaxial system to be used in some cases.…”
Section: Introductionmentioning
confidence: 99%